Associations of maternal smoking and drinking with fetal growth and placental abruption. (October 2020) - Odendaal, Hein; Wright, Colleen; Schubert, Pawel; Boyd, Theonia K.; Roberts, Drucilla J.; Brink, Lucy; Nel, Daan; Groenewald, Coen
Abstract: Objective: To investigate pregnant women from the Safe Passage Study for the individual and combined effects of smoking and drinking during pregnancy on the prevalence of clinical placental abruption. Study design: The aim of the original Safe Passage Study was to investigate the association of alcohol use during pregnancy with stillbirths and sudden infant deaths. Recruitment for this longitudinal study occurred between August 2007 and October 2016. Information on smoking and drinking was collected prospectively at up to 4 occasions during pregnancy where a modified timeline follow-back method was used to assess the exposure to alcohol. Placentas were examined histologically in a subset of pregnant women. For this study we examined the effects of smoking and drinking on fetal growth and the prevalence rate of placental abruption. High smoking constituted of 10 or more cigarettes per day and high drinking of four or more binge drinking episodes or 32 and more standard drinks during pregnancy. Placental abruption was diagnosed in two ways, by the clinical picture or the macroscopic and microscopic examination of the placenta. Results: When compared to the non-drinking/non-smoking group, the high drinking/high smoking group were significantly older, had a higher gravidity, had a lower household income and booked later for prenatal care; fewer of them were employed and had toilet and running water facilities in their houses. Clinical placental abruption was diagnosed in 49 (0.87 %) of 5806 pregnancies. Histological examination was done in 1319 placentas; macroscopic and microscopic diagnosis of placental abruption was made in 8.2 % and 11.9 % of placentas respectively. These 49 cases were then correlated with seven smoking/drinking patterns during pregnancy. When compared to rates for no smoking/no drinking (0.11 %) and low smoking/no drinking (0.55 %), the prevalence rate of placental abruption was significantly higher (p < .005) in the low smoking/low drinking group (1.25 %). There was also a significant relationship between low maternal employment and methamphetamine use with placental abruption. Conclusion: As many conditions and habits are associated with placental abruption, it is impossible to single out one specific cause but concomitant drinking and smoking seem to increase the risk of placental abruption.